Problems in measuring portfolio performance An application to contrarian investment strategies - Ball, Ray; Kothari, S.P.; Shanken, Jay (Journal of Financial Economics, 1995)
We document problems in measuring raw and abnormal five-year contrarian portfolio returns. ‘Loser’ stocks are low-priced and exhibit skewed return distributions. Their 163% mean return is due largely to their lowest-price quartile position. A $18-th price increase reduces the mean by 25%, highlighting their sensitivity to micro-structure/liquidity effects. Long positions in low-priced loser stocks occur disproportionately after bear markets and thus induce expected-return effects. A contrarian portfolio formed at June-end earns negative abnormal returns, in contrast with the December-end portfolio. This conclusion is not limited to a particular version of the CAPM.